Kurikulum Merdeka dalam Perspektif Filsafat Konstruktivisme - Hakiky, Nur; Nurjanah, Siti; Fauziati, Endang (TSAQOFAH, 2023)
The dynamics of learning in Indonesia are very dynamic accompanied by increasingly rapid technological developments. The purpose of this study is to describe an independent curriculum that carries the concept of independent learning in the perspective of constructivism philosophy. The method used in this research is library research using a philosophical approach (analyzing the constructivism philosophy of the independent curriculum). The data collection technique used is the documentation technique which is carried out by collecting data sourced from books in libraries and the internet, as well as articles and journals related to various writings in research. The results of this study indicate that the independent curriculum that carries the concept of independent learning is very much in line with the philosophical theory of constructivism which encourages teachers and students to construct their own knowledge. The learning process is highly emphasized to create innovations that can motivate students to build their own learning experiences according to conditions. The curriculum that carries the concept of independent learning emphasizes student-centered learning (student center), the teacher is no longer a center of learning but a facilitator who helps facilitate students to explore their own knowledge, chooses a learning style that suits them, gives complete freedom to students to be able to grow a character that is brave, confident, independent, and disciplined.